Веб-система для відстеження вмісту алергенів у повітрі - Клочко, О. Ю. (ХНУРЕ, 2021)
Today we hear more and more about the problems of ecology and environmental pollution. Doctors have found a direct link between the growing number of people suffering from allergies and asthma and the deteriorating environmental situation in the region. However, for accurate information, it is important not only to determine the timing of flowering of the plant, but also to study the relationship between meteorological factors and changes in the amount of pollen of this plant in the air. The main idea is to develop a system that will help track these data for further processing, predict their concentration, monitor human health, prevent disease exacerbations and simplify the lives of allergy sufferers.
Науковий керівник – ст. викл. Широкопетлєва М.С.
Keywords: веб-система; відстеження алергенів у повітрі